German medical data sciences: visions and bridges : proceedings of the 62nd annual meeting of the German Association of Medical Informatics, Biometry and Epidemiology (gmds e.V.) 2017 in Oldenburg (Oldenburg) - GMDS 2017 - Röhrig, Rainer (Studies in health technology and informatics, 2017)
We live in an age characterized by computerized information, but ubiquitous information technology has profoundly changed our healthcare systems and, if not adequately trained to deal with it, healthcare professionals can all too easily be overwhelme...